NANOSCIENCE CURRICULUM IN SCHOOL EDUCATION INTEGRATING NANOSCIENCE INTO THE CLASSROOM - Ravichandran, R.; Sasikala, P. (SCHOOL SCIENCE, 2010)
Learning does not just mean studying for addition to qualifications or to improve job opportunities. It should be geared up to open up one's mental abilities to explore a wide range of activities thatfacilitate widening the horizon of understanding nature and natural phenomena besides expanding scope for and physical opportunities. NCERT is committed to building a world-class education and training framework. In order to accomplish its mandate for improving the quality of school education it strives continuously to develop, upgrade and modernise school curriculum, assessments and examinations. Main objective of these interventions is to provide a coherent and integrated curriculum and assessment framework for schools, which, in turn, may raise standard of achievement and widen educational opportunity.